Trends and determinants of modern contraceptive utilisation among adolescent girls aged 15-19 years in Sierra Leone: an analysis of Demographic and Health Surveys, 2008-2019 - Emmanuel Olal; Fassou Mathias Grovogui; Ritah Nantale; Quraish Sserwanja; Chola Nakazwe; Lilllian Nuwabaine; David Mukunya; Eric Nzirakaindi Ikoona; Lenka Benova (Journal of Global Health Reports)
# Background